Evaluating public participation in Denmark's water councils: How policy design and boundary judgements affect water governance!. (December 2016) - Graversgaard, Morten; Thorsøe, Martin Hvarregaard; Kjeldsen, Chris; Dalgaard, Tommy
Under the Water Framework Directive, public participation was identified as a key part of water planning. This caused a paradigm shift in Danish water planning. Water councils in River Basin Districts were established to provide public input on how to improve the physical conditions in streams. A study of the water councils found that Denmark has complied with the requirements of making background information available to the public and ensuring consultation. The facilitation of the councils' processes has worked well. However, while they are presented as the 'new governance option' in Danish water planning, this does not accord with reality. The water council processes are limited in scope and controlled by the central government. Their process can be better characterized as expanded stakeholder consultation, officially part of the policy process but involving very little active public involvement. The article concludes by indicating the consequences for participation and collaborative innovation.